Tri Hita Karana Philosophy in Revealing The Concept of Green Accounting (Phenomenological Study). - Kusumawati, Ni Putu Ayu; Pramuki, Ni Made Wisni Arie; Pratiwi, Ni Putu Trisna Windika (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2023)
Sustainability issues that have spread recently have also had an impact on the world of accounting. Previously, the company's annual financial reporting was the prima donna, but now a sustainability report has been added as a response to this issue and provides consequences for the emergence of the green accounting concept. Green accounting develops from the basic philosophy that accountants must care about the environment and society. The development of accounting which had moved away from the focus on social and environmental relations has created a problem because accounting is only focused on technical matters and becomes apathetic towards conditions in the surrounding environment. Through the Tri Hita Karana philosophy phenomenological study method, researchers are trying to reveal how the concept of green accounting is based on values derived from the teachings of Hinduism. Researchers analyzed data from informants by conducting interviews with experienced subjects in the field of green accounting and interviewing knowledgeable subjects from accountants, humanists and religionists. The selection of the method is specific in order to reveal the values of Hinduism in the concept of green accounting. The concept of green accounting with a phenomenological approach to the Tri Hita Karana philosophy includes 3 main aspects that influence green accounting motives, reporting, recording, summarizing, and recognition. The srada bhakti, yadnya and spiritual aspects complement the green accounting concept which intends to carry out as best as possible the social and environmental responsibility of an entity. The results of the green accounting concept through the phenomenological approach to the THK philosophy raises a more comprehensive epistemological face because it contains basic aspects that previously did not exist in the conventional green accounting concept.